PENGARUH PERTUMBUHAN PENJUALAN, LEVERAGE OPERASI, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftardi BEI Periode Tahun 2014-2015) - Fauziah, Fitri; Halim, Abdul; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2018)
This study aims to examine and explain the partial and dominant influence of Sales Growth, Operating Leverage, Profitability and Company Size on the Financial Structure of companies listed on the Indonesia Stock Exchange (IDX). The analytical method used is a quantitative method by testing classical assumptions and statistical analysis, namely multiple linear regression analysis. The sampling method used was purposive sampling. This research variable consists of sales growth, operating leverage, profitability and company size as independent variables and financial structure as the dependent variable with a total sample of 36 manufacturing companies. The analysis shows that sales growth, profitability, and company size affect the financial structure while operating leverage has no effect on the financial structure and profitability has the most dominant influence on the financial structure